Research progress of Traditional Chinese Medicine nursing technology in patients with early-stage acute mastitis (中医护理技术在急性乳腺炎早期患者中的应用研究进展) - ZENG Yijun (曾亦君); ZHANG Pengwei (张鹏炜); YANG Sijia (杨思佳); YE Chunhong (叶春红); LI Li (李力) (中西医结合护理)
Traditional Chinese Medicine nursing technology has proven to be effective in relieve the clinical symptoms and improve the recovery of patients with acute mastitis. This paper reviewed studies on application status of Traditional Chinese Medicine nursing technology in patients with early-stage acute mastitis, provides approaches for the nursing of acute mastitis and promote the Traditional Chinese Medicine nursing technology in clinical practice. (中医护理措施具有疏通经络和排乳止痛的功效, 能够改善急性乳腺炎患者的临床症状, 促进疾病转归。本研究就中医护理技术在急性乳腺炎早期患者中的应用现状进行综述, 以期拓展对急性乳腺炎患者的护理新思路, 进一步推动中医护理技术在急性乳腺炎早期患者中的应用。)